TEMPORAL SEMANTICS OF VERBAL FORMS IN SURAH AL-BAQARAH: A LINGUISTIC ANALYSIS AND ITS PEDAGOGICAL IMPLICATIONS FOR ARABIC GRAMMAR INSTRUCTION - muhammad zaenuri; Nafisa Zeni Agustin; Machmud Yunus; Muhammad Zaky Sya'bani (ALLAIS Journal of Arabic Language and Literature, 2025)
This study analyzes the temporal representation of verbs (fi'il) in Surah al-Baqarah and how the meaning of time is understood and translated into Indonesian. Using qualitative-descriptive methods and data from the mushaf of the Qur'an and the official translation of the Ministry of Religion of the Republic of Indonesia, this study examines fi’il māḍī and muḍāri' morphosyntaxically, semantically, and pragmatically. The results show that temporal representations in the Qur'an are not linear and literal as in traditional Arabic grammar, but rather contextual and dynamic. Fi’il māḍī and muḍāri' have a flexibility of the meaning of time that depends on the context of syntax, qarīnah, and rhetorical functions in discourse. On the translation side, the Indonesian version generally adjusts the verb tense literally, but shifts in meaning often occur due to differences in language structure. Therefore, understanding the meaning of Qur'anic verbs requires an integrative approach between linguistic analysis and translation strategies. The implications of this research emphasize the importance of teaching nahwu al-Qur'an that combines grammatical aspects with pragmatic contexts and discourse to produce a deeper and more accurate understanding of the text.